2019
DOI: 10.1002/acr2.11079
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Adherence to Oral Methotrexate Measured Electronically in Patients With Established Rheumatoid Arthritis

Abstract: ObjectiveTo assess methotrexate (MTX) adherence using the Medication Event Monitoring System (MEMS) and characterize associations with adherence in patients with rheumatoid arthritis (RA).MethodsEligible patients participated in Forward, the National Databank for Rheumatic Diseases, and recently (12 months or sooner) initiated oral MTX. MEMS was used to compile MTX weekly dosing over 24 weeks. The Beliefs about Medicines Questionnaire (BMQ) was completed, and baseline demographics and disease characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In summary, pharmacokinetic modeling indicates that, for the median patient, the predominant pattern of missed MTX doses after starting MTX, ie, one of isolated, single missed doses, 10 would have little clinical effect, other than delaying the time to reach the therapeutic threshold and/or steady state. For the median patient at steady state, 3 consecutive missed doses would be required for MTXglu levels in red blood cells to fall below the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, pharmacokinetic modeling indicates that, for the median patient, the predominant pattern of missed MTX doses after starting MTX, ie, one of isolated, single missed doses, 10 would have little clinical effect, other than delaying the time to reach the therapeutic threshold and/or steady state. For the median patient at steady state, 3 consecutive missed doses would be required for MTXglu levels in red blood cells to fall below the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Patterns of missed MTX doses over 24 weeks in clinical practice were extracted from a study of adherence in patients participating in the National Data Bank (NDB) for rheumatic diseases. 9 , 10 Adherence data were measured using a Medication Event Monitoring System (MEMS) and presented in the form of a “heat map”, a color-coded graph of the number of doses taken each week by each patient. 10 Dosing patterns were used for selected patients with instances of single missed doses (patients 006, 0021, 0034), or of 2 consecutive (patients 0017, 0027) or 3 consecutive (patients 008, 0011) missed doses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, previous research revealed that medication adherence to DMARDs ranged from 30-107%, depending on the measurement methods used to assess medication-taking behavior. [3][4][5] Non-adherence to DMARDs is associated with higher disease activity scores and an increased risk of radiographic damage. 2,[6][7][8] Since irreversible articular damage mainly occurs early in the course of RA, with most rapid radiologic progression during the first two years after diagnosis, it is likely that patients with early RA will benefit most from adherence-improving interventions.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Electronic devices, such as Medication Event Monitoring Systems (MEMS), register time intervals between consecutive openings of MEMS bottles and, therefore, provide insight in medication adherence patterns of patients based on device usage. 5 , 14 , 16 , 17 These data can be used to (1) confront patients with their own medication-taking behavior, and (2) support healthcare professionals in providing tailored and non-judgmental feedback. 14 Such feedback includes the elicitation and strengthening of patients' intrinsic motivation to overcome practical and perceptual barriers to adequate medication intake in daily life (eg concerns about the prescribed medication and beliefs related to medication necessity), and to overcome knowledge gaps regarding DMARD treatment.…”
Section: Introductionmentioning
confidence: 99%